Scientific and Regulatory Policy Committee Points to Consider*: The Toxicologic Pathologist's Role in the 3Rs. (October 2019) - Hukkanen, Renee R.; Dybdal, Noel; Tripathi, Niraj; Turner, Patricia V.; Troth, Sean P.
Pathologists are trained medical professionals with special expertise in diagnostics, research, and pathophysiology. In these roles, pathologists are well qualified and positioned to engage in conversations about animal use replacement, reduction, and refinement (3Rs), thereby championing the guiding principles of the 3Rs. In particular, toxicology or nonclinical safety assessment is an important area where the discipline of toxicologic pathology can have a critical role in adopting 3Rs principles. As such, a working group of the Society of Toxicologic Pathology Scientific and Regulatory Policy Committee was formed to investigate and summarize some of the areas where veterinary pathologists working in the field of toxicology can increase involvement and impact on 3Rs. This "Points to Consider" publication provides an overview of areas within toxicology where the veterinary pathologist's perspective may maximize animal value, including refinement of study design, optimizing sample collection, the development of 3Rs focused regulatory policy, and humane end point determination.* This Points to Consider article is a product of a Society of Toxicologic Pathology (STP) Working Group commissioned by the Scientific and Regulatory Policy Committee (SRPC) of the STP. It has been reviewed and approved by the SRPC and Executive Committee of the STP, but it does not represent a formal Best Practice recommendation of the Society; rather, it is intended to provide key "points to consider" in designing nonclinical studies or interpreting data from toxicity and safety studies intended to support regulatory submissions. The points expressed in this document are those of the authors and do not reflect views or policies of the employing institutions. Readers of toxicologic pathology are encouraged to send their thoughts on these articles or ideas for new topics to the editor.